From the Front Lines At Seoul Bank : Restructuring and Reprivatization - Kang, Chungwon (Washington, D.C. : International Monetary Fund, 2003)
Soon after Korea agreed to an IMF-supported program, Seoul Bank and Korea First Bank were nationalized through an injection of public funds by the government. The two banks were singled out early in the IMF-supported program to be sold to foreign investors. Korea First Bank was sold to foreign investors at the end of 1999. Seoul Bank, however, remained a government-owned bank, managed by a team of professionals recruited from outside of the traditional banking sector. This paper describes the restructuring of Seoul Bank by the new management team between June 2000 and October 2002, when the bank was sold to Hana Bank in a merger transaction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet